Constraining superheavy decaying dark matter with directional ultra-high energy gamma-ray limits. Issue 11 (8th November 2021) - Kalashev, O.; Kuznetsov, M.; Zhezher, Y.
Abstract: We present constraints on the lifetime of the superheavy decaying dark matter branching to the qq̅ channel in the mass range 10 19 –10 25 eV based on the directional limits on the ultra-high-energy (UHE) gamma rays from dwarf spheroidal galaxies (dSphs) and the Milky Way (MW) centre obtained by the Pierre Auger Observatory and the Telescope Array experiment. Attenuation effects during the propagation of UHE photons towards Earth are taken into account. The strongest constraints are derived for the MW centre and have an order of 10 20 yr. We conclude that the UHE diffuse gamma-ray limits provide more efficient signature for the superheavy DM search than the directional gamma-ray limits.